2022
DOI: 10.31083/j.fbl2702040
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal nanomaterials for the diagnosis and treatment of hematological malignancies

Abstract: Background:Recently, the incidence of hematological malignancy, such as various leukemias, multiple myeloma and lymphoma, has revealed an increasing tendency, exhibiting a major impact on human health. Most of the available anti-cancer drugs, however, possess high non-targeted accumulation, dosage-associated toxicity, fast elimination, and lack specificity towards tumors, which restrict their utilization in clinical therapy. This extends also to cancer diagnosis where there is a lack of predictive biomarkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 128 publications
0
11
0
Order By: Relevance
“…Because of this heterogeneity, there is no unified standard diagnostic method for their diagnosis and treatment ( Bochtler et al, 2018 ). In recent years, although there have been an increasing number of diagnostic procedures for hematological tumors, with the development of Raman spectroscopy and its wide application in many fields, its value in the diagnosis of tumor biology is also increasing ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this heterogeneity, there is no unified standard diagnostic method for their diagnosis and treatment ( Bochtler et al, 2018 ). In recent years, although there have been an increasing number of diagnostic procedures for hematological tumors, with the development of Raman spectroscopy and its wide application in many fields, its value in the diagnosis of tumor biology is also increasing ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Huang et al ( 2022) [34] reported on the applications of metal nanomaterials in the diagnosis and treatment of HMs. However, detailed discussions on GNMs were not observed in that review [34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Huang et al ( 2022) [34] reported on the applications of metal nanomaterials in the diagnosis and treatment of HMs. However, detailed discussions on GNMs were not observed in that review [34]. In the current review, we included research articles published before February 2021 that covered our topics of interest (i.e., GNMs and HMs).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the Our World in Data website shows that an estimated 9.6 million people died of various forms of cancer in 2017. With the rising morbidity and mortality, cancer is a serious threat to human health and has become a major global public health problem [3]. Therefore, it is imperative that the search for effective cancer drugs is accelerated.…”
Section: Introductionmentioning
confidence: 99%